The Effect of the Tongyang Huoxue Recipe (TYHX) on the Ito/IKur in Ischemia/Reperfusion Sinoatrial Node Cells - Yanli Wang; Qiaomin Wu; Jinfeng Liu; Ruxiu Liu (Hindawi-Wiley, 2022)
Background. The transient outward potassium current (Ito) and the ultrarapid delayed rectifier potassium current (IKur) are major potassium currents involved in the repolarization process of sinoatrial node cells (SNCs). Methods and Results. The SNCs of neonatal rats were divided into control, ischemia/reperfusion (I/R), I/R+blank serum, and Tongyang Huoxue recipe (TYHX) serum groups. Ito and IKur were recorded using the whole cell patch-clamp technique, and the current-voltage (I-V), steady-state activation (SSA), steady-state inactivation (SSI), and recovery from inactivation (RFI) curves were plotted, respectively. Compared to the control group, both the peak current density and the current density at the voltage of Ito and IKur decreased obviously in SNCs after simulated I/R, the SSA curves moved right, and the SSI curves moved left. After TYHX was added to the extracellular solution of SNCs, both the peak current density and the current density at the voltage of Ito and IKur increased significantly, the SSA curves moved left, and the SSI curves moved right with a significant difference of V1/2. The recovery from the IKur RFI curves was slightly restored, and the Ito curves did not change. Conclusions. TYHX increases the peak current density, accelerates the activation, and decreases the inactivation of the Ito and IKur. This may be the mechanism of TYHX in shortening the action potential duration of repolarization, which accelerates spontaneous pulsation.